Pengaruh Kepercayaan dan Keahlian Streamer terhadap Minat Pembelian Konsumen Pengguna TikTok di Kota Samarinda - Khairun Mubarak; Marsha Anindita; Istimaroh Istimaroh (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of trust and streamer expertise on consumer purchase intention among TikTok users in Samarinda City. A quantitative approach was employed using a survey method involving 102 respondents who were active TikTok live users. Data collection was carried out through questionnaires using a 1–6 Likert scale. The data were analyzed with the aid of SPSS version 26.0, through a series of statistical tests including validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity) to ensure regression assumptions were met, and hypothesis testing (multiple linear regression, partial, simultaneous, and coefficient of determination tests). The results showed that both trust and streamer expertise have a positive and significant effect on consumer purchase intention, both partially and simultaneously. These findings indicate that the higher the level of trust and expertise possessed by the streamer, the greater the consumer’s tendency to make a purchase. The implications of this research may serve as a strategic reference for business practitioners in utilizing the TikTok live feature as an effective digital marketing medium tailored to the characteristics of local consumers.